10x-3(x-6)=-(x-1)
first distribute
10x -3x +18 = -x + 1
then you simplify
7 x +18 = -x +1
then you leave of when one side of x
6 x +18= +1
use opposite operation on the side with the x and do the same equation to the other side
6 x = -17
then divide
x = - 2.8333....
12r=156
Answer r=13
it will help you
Answer:
b
Step-by-step explanation:
Answer:
Yes
Step-by-step explanation:
First step of a synthetic divison is that we need to carry down the leading coefficient. Here the leading coefficient is 2. So, carry down 2 at the bottom.
Next step is to multiply the divisor -3 with this carry down number 2. So, we have got 3*(-2)= -6 which will place atthe bottom of the next coefficient 4.
Next step is to add this column.
Now repeat the same method again till the last colum.
At the end we have got 0 after the addition. Which means the remainder is 0.
So, the quotient is 2x^2-2x+2.